Prevalence study on self-declared work accidents in areas covered by family health strategies: A cross-sectional study - Pereira, Karen Thalita [UNESP]; Silva, Ana Carolina Rodrigues de Sá [UNESP]; Silva, Luiz Felipe (FapUNIFESP (SciELO), 2020)
BACKGROUND: Occupational accidents are a complex phenomenon and a major public health problem. Occupational health surveillance actions are essential for prevention of injuries of this nature. OBJECTIVE: To ascertain the prevalence of and the variables associated with occupational accidents in the city of Itajubá (MG). DESIGN AND SETTING: A cross-sectional study with a quantitative approach, based on a household survey with random sampling, was conducted in areas covered by the Family Health Strategy (FHS) in Itajubá (MG). METHODS: Questionnaires were applied to 292 people. The data were analyzed by means of logistic regression. RESULTS: The prevalence of occupational accidents was 8.6%. The underreporting rate was 60.0%. The sce-nario for these accidents, according to the model established through the regression analysis, was most likely to involve males who declared their skin color as white and who did not have a formal employment contract. CONCLUSION: This study makes a contribution towards unveiling the relationship between healthcare and work, and thus serve as support for the development of strategies to prevent underreporting. Lastly, the results provide the basis for future public health intervention actions and for future studies.
Keywords: Accident prevention; Accidents; Occupational; Occupational health; Public health